PMM.85 Radiation considerations for catheter directed thrombolysis in iliofemoral thrombosis n pregnancy. (9th June 2014) - Meththananda, I; Thapar, A; Moore, HM; Anwar, M; Davies, AH
Abstract : Background: Venous thromboembolism remains the direct cause of maternal death in the UK. Current Royal College of Obstetricians and Gynaecologist's guidelines for confirmed deep vein thrombosis (in acute maternal collapse) carry significant risks of miscarriage (5.8%), haemorrhage (8.1%) and mortality (1.2%). Anaesthetic risks of thrombectomy include low birth weight and miscarriage. Catheter directed thrombolysis (CDT) is an infrequent consideration in these patients. Case Presentation: 34 year old, 13-week pregnant lady presented with an 8-day history of acute onset painful lower left leg swelling and erythema, which rendered her wheelchair bound. She had no personal thromboembolic risk factors except a maternal history of DVT and venous ulceration. An extensive thrombus from left common femoral to popliteal vein was confirmed on duplex ultrasound, with occlusion of the profunda vein. After discussion in the multi-disciplinary meeting it was thought that the thrombus technically amenable to CDT for relief of disabling symptoms. Risk of pelvic irradiation was assessed on current Royal College of Radiologists Guidance (2009) and the International Commission on Radiological Protection Report 84 (2000). The foetal dose from the procedure would be 175–245 mGy. This would give an excess childhood cancer risk of 1.3–2%, compared with a background incidence of 0.2%. This dose was significantly greater than the limit for major organ malformations. The patient was thus prescribed treatment dose LMWH and compression and remains well to date. Discussion: The period from 8–15 weeks is the most radiation sensitive period to the foetus. Catheter directed thrombolysis maybe a more viable treatment option from gestation 16 weeks when risks to foetal central nervous system risks are reduced.